Implementasi Metode Blended Learning Dalam Pendidikan Jasmani - Ana Purnama, Fira Anatasya, La Ode Muhammad Wahyu, Ilfan Rahyul, Suryani, Resky Ana Abadi (Jurnal Ilmu Sosial Dan Pendidikan, 2024)
Abstract Blended learning is a learning approach that combines two or more different learning methods, such as face-to-face learning and online learning. Technology is an integral component in blended learning, both as a tool for presenting learning material and for communicating and interacting between lecturers and students. Implementing the blended learning method in physical education is a progressive step that can improve the quality of learning. Blended learning combines online learning with direct face-to-face learning. In the context of physical education, this approach can provide benefits, especially in developing students' motor and cognitive skills. The current digital era has had an extraordinary positive impact on the world of education and has an impact on how lecturers provide different learning services than usual through technology-based learning models.